Correction: EUS-Guided Biliary Drainage Versus ERCP for the Primary Palliation of Malignant Biliary Obstruction: A Multicenter Randomized Clinical Trial. (October 2018) - Paik, Woo; Lee, Tae; Park, Do; Choi, Jun-Ho; Kim, Seon-Ok; Jang, Sunguk; Kim, Dong; Shim, Ju; Song, Tae; Lee, Sang; Seo, Dong-Wan; Lee, Sung; et al.
There was an error made in the first paragraph of the Results section, under the subheading 'Study Population'. The original sentence said: A total of 64 patients underwent ERCP, and 61 patients underwent EUS-BD. The correct sentence is as follows: A total of 61 patients underwent ERCP, and 64 patients underwent EUS-BD. The authors would like to apologize for the error.